Phenolic diterpenes from Rosemary supercritical extract inhibit non-small cell lung cancer lipid metabolism and synergise with therapeutic drugs in the clinic - Bouzas, Adrián; Gómez de Cedrón, Marta; Colmenarejo, Gonzalo; Laparra-Llopis, José Moisés; Moreno-Rubio, Juan; Montoya, Juan José; Reglero, Guillermo; Casado, Enrique; Tabares, Beatriz; Sereno, María; Ramírez de Molina, Ana (Frontiers in Oncology, 2022)
Lung cancer is one of the most deadly and common cancers in the world. The molecular features of pa-tient’s tumours dictate the different therapeutic decisions, which combines targeted therapy, chemotherapy, and immunotherapy. Altered cellular metabolism is one of the hallmarks of cancer. Tumour cells reprogram their metabolism to adapt to their novel requirements of growth, proliferation, and survival. Together with the Warburg effect, the role of lipid metabolism alterations in cancer development and prognosis has been highlighted. Several lipid related genes have been shown to promote transformation and progression of cancer cells and have been proposed as biomarkers for prognosis. Nevertheless, the exact mechanisms of the regulation of lipid metabolism and the biological consequences in non-small cell lung cancer (NSCLC) have not been elucidated yet. There is an urgent necessity to develop multidisciplinary and complementary strategies to improve NSCLC patients´ well-being and treatment response. Nutrients can directly affect fundamental cellular processes and some diet-derived ingredients, bioactive natural compounds and natural extracts have been shown to inhibit the tumour growth in preclinical and clinical trials. Previously, we described a supercritical extract of rosemary (SFRE) (12 - 16 % composition of phenolic diterpenes car-nosic acid and carnosol) as a potential antitumoral agent in colon and breast cancer due to its effects on the inhibition of lipid metabolism and DNA synthesis, and in the reduction of resistance to 5-FluoroUracil (5-FU). Herein, we demonstrate SFRE inhibits NSCLC cell bioenergetics identifying several lipid metabo-lism implicated targets. Moreover, SFRE synergises with standard therapeutic drugs used in the clinic, such as cisplatin, pemetrexed and pembrolizumab to inhibit of cell viability of NSCLC cells. Importantly, the clinical relevance of SFRE as a complement in the treatment of NSCLC patients is suggested based on the results of a pilot clinical trial where SFRE formulated with bioactive lipids (PCT/ES2017/070263) dimin-ishes metabolic and inflammatory targets in peripheral-blood mononuclear cells (PBMC), such as MAPK (p=0.04), NLRP3 (p=0.044), and SREBF1 (p=0.047), which may augment the immune antitumour func-tion. Based on these results, SFRE merits further investigation as a co-adjuvant in the treatment of NSCLC.